Pencetakan Al-Qur’an dari Venesia Hingga Indonesia - Hamam Faizin (UIN Sunan Kalijaga Yogyakarta, 2011)
The absence of study on history of Qur’an printing in some Ulumul Qur’an (Qur’anic Studies)books is the evidence that the muslim scholars did not much concern on history of Qur’an printing due to it had nothing to do with the authenticity of Qur’an. Whereas, historically many conflicts, motives, pro and contra appeared in accepting the printing qur’an. In addition, whatever the muslim attitudes to respond the moveable type of print, the West has constributed to the spreading of Qur’an around the world. As muslim appreciation, this article tries to cover simply and briefly the history of printing Qur’an from Venice printing version to Indonesian version.